PEMBELAJARAN BERBICARA UNTUK MEMBANGUN KOMUNIKASI BELAJAR EFEKTIF - Dahliah Patiung (Faculty of Tarbiyah and Teacher Training Universitas Islam Negeri Alauddin Makassar, 2016)
Speaking in formal situations is not easy. Even the intelligent and educated persons are not necessarily adept and skillful in speaking. Many of us, especially students who are still afraid to speak in front of many people, even speaking in front of their friends. In interacting activity, of course, it takes strategy so that the message conveyed to listeners can be received and understood. Communication activities can be divided into two domains, namely formal and non-formal. Communication in the formal domain means to communicate information to the other person in an official forum with a specific theme and with manners as well as the official costume. This activity is usually manifested in the form of speaking in front of people or forums. Communicated in the non-formal domain means to convey information to listeners in informal situations. The scientific term of activities may be regarded as public speaking or speaking in front of people.